DIVERSION AS THE CASE RESOLUTION FOR CHILDREN IN CONFLICT WITH THE LAW WITHIN THE PERSPECTIVE OF LEGAL PSYCHOLOGY - Chamdani; Indradjaja, Nobella; Nurhandy, Febrina (Awang Long Law Review, 2024)
Children have an important role in life, so children's problems are initially personal problems, namely the relationship between parents and their children. Children in conflict with the law are children who are in conflict with the law, children who are victims of criminal acts, and children who are witnesses to criminal acts. ABH must be viewed comprehensively, both sociologically, psychologically and formally juridically. If done carefully, we will achieve comprehensive protection of children's rights and human rights. The method used in this research is normative research with a statutory and psychological approach in analyzing the data. The existence of a child rights convention which contains international regulations which have been adapted into national law in the form of a law is often frightening when viewed from the perspective of "protecting behind the law". Diversion is mandatory at every level in Article 7 that at the level of investigation, prosecution and examination of children's cases in district courts, diversion must be attempted.